STUDI KONTRIBUSI RETRIBUSI PADA PENDAPATAN ASLI DAERAH (PAD) KABUPATEN POSO TAHUN 2015 - Maid, Abdul (Katalogis, 2017)
The research aims to find out and explain trend of local retribution growth and its realization of on local revenue of Poso regency in the period of 2010 to 2015. To achieve it, the researcher use qualitatife descriptif method to see the effect ofthe local retribution cover: general service retribution, business service retribution and certain license retribution on local revenue. The research results indicate that partially general service retribution and business retribution give positive effect on local revenue, while the certain license retribution does not affect onlocal revenue. For the further research it is expected to have a longer fiscal yeal that it makes a better time series data and it can be seen clearly the effect from one period to others. For local goverment, it is expected to be consistent applying the rule for the retribution implementation. One source of local revenue is local retribution tax which is needed to be increased. Increasing supervision function and awareness for implementer in the field, so the target is always be fulfilled and achieved by the local revenue, economic growth in Poso regency will be increased.